2003
DOI: 10.1073/pnas.0237327100
|View full text |Cite
|
Sign up to set email alerts
|

Optimized expression and specific activity of IL-12 by directed molecular evolution

Abstract: DNA delivery of IL-12 has shown promise in reducing the toxic side effects associated with administration of recombinant human (h)IL-12 protein while maintaining the ability to inhibit tumor growth and abolish tumor metastases in animal models. We have developed a more potent version of IL-12 by using DNA shuffling and screening to improve its expression in human cells and specific activity on human T cells. The most improved evolved IL-12 (EvIL-12) derived from seven mammalian genes encoding both the p35 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
8

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 57 publications
0
12
0
8
Order By: Relevance
“…For example, the products of recombination between two distantly related b-lactamases retained function with significantly higher probability than b-lactamase variants that involved the same number of amino acid changes as introduced by recombination, but where these changes were introduced through random point mutation (Drummond et al 2005). More anecdotally, a DNA shuffling experiment involving divergent interleukin-12 genes from seven mammalian species showed that between 40 and 90% of chimeric molecules retained interleukin-12 activity (Leong et al 2003). A similar study creating four random recombinant ainterferons from 20 different human a-interferon genes that differ, on average, at 17 amino acid positions, found that all four recombinant proteins generated were as active as their ''parents.''…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the products of recombination between two distantly related b-lactamases retained function with significantly higher probability than b-lactamase variants that involved the same number of amino acid changes as introduced by recombination, but where these changes were introduced through random point mutation (Drummond et al 2005). More anecdotally, a DNA shuffling experiment involving divergent interleukin-12 genes from seven mammalian species showed that between 40 and 90% of chimeric molecules retained interleukin-12 activity (Leong et al 2003). A similar study creating four random recombinant ainterferons from 20 different human a-interferon genes that differ, on average, at 17 amino acid positions, found that all four recombinant proteins generated were as active as their ''parents.''…”
Section: Discussionmentioning
confidence: 99%
“…The authors estimate that mutating the same number of positions as are changed in a recombination event among these proteins would abolish protein function (Chang et al 1999). Such weak deleterious effects may contribute to the promise recombination shows in engineering new proteins (Stemmer 1994;Crameri et al 1997Crameri et al , 1998Zhang et al 1997;Chang et al 1999;Kolkman and Stemmer 2001;Leong et al 2003;Raillard et al 2001a,b). Because recombination can reorganize genetic systems on a much larger scale than point mutations, these weak effects on different levels of organization are intriguing.…”
Section: Discussionmentioning
confidence: 99%
“…Directed evolution has been used to change the activity, selectivity, or stability of enzymes (reviewed in Refs. 5 and 6) but also to improve viral vector stability (7), cytokine efficacy (8), and antibody fragment binding (9). Recently, Yokobayashi et al (10) successfully applied directed evolution to genes comprising a simple genetic circuit and demonstrated that a nonfunctional circuit containing improperly matched components could evolve rapidly into a functional one (10,11).…”
mentioning
confidence: 99%
“…Toxic side effects have been associated with the direct administration of recombinant antitumor interleukin-12 protein. A DNA vaccine based on the interleukin-12 gene has been shown to reduce adverse side effects, while its potency and effectiveness have been further improved by directed evolution (179). In addition, high-affinity T-cell receptor variants can be generated and used for detecting peptidemajor histocompatibility complex complexes on antigen-presenting cells (121).…”
Section: Directed Evolution Of Pharmaceuticalsmentioning
confidence: 99%